An Extremely Simple Method for Protecting Lithium Anodes in Li‐O2 Batteries - Zhang, Xin; Zhang, Qinming; Wang, Xin‐Gai; Wang, Chengyi; Chen, Ya‐Nan; Xie, Zhaojun; Zhou, Zhen (Angewandte Chemie International Edition, 2018)
Rechargeable Li‐O2 batteries have aroused much attention for their high energy density as a promising battery technology; however, the performance of the batteries is still unsatisfactory. Lithium anodes, as one of the most important part of Li‐O2 batteries, play a vital role in improving the cycle life of the batteries. Now, a very simple method is introduced to produce a protective film on lithium surface via chemical reactions between lithium metals and 1,4‐dioxacyclohexane. The film is mainly composed of ethylene oxide monomers and endows Li‐O2 batteries with enhanced cycling stability. The film could effectually reduce the morphology changes and suppress the parasitic reactions of lithium anodes. This simple approach provides a new strategy to protect lithium anodes in Li‐O2 batteries. Protective coating: The stability of lithium anodes plays a vital role in improving the cycle life of Li‐O2 batteries. A convenient method is presented to produce a film on a lithium surface by chemical reactions between lithium metal and 1,4‐dioxacyclohexane. The protective film could reduce the morphology changes and suppress the parasitic reactions of lithium anodes and endow Li‐O2 batteries with enhanced cycling stability.